Impacto del blog en la producción de textos argumentativos en estudiantes de educación secundaria - Chura Quispe, Gilber (2022)
The research problem is focused on the deficiencies in the production of argumentative texts (PAT) in high school education. The aim of the study is determining if the application of the blog, improves the  PAT level in high school education students from the 4th and 5th   of secondary level in a  school of Tacna. The research was an applied type with a pre-experimental design. Non-probability sampling was employed among 32 students from 4th  and 5th  of secondary level  which were selected intentionally. The instrument was a rubric to evaluate the PAT, which was validated by expert judgment. The results show an increase to 65,62% of students at the satisfactory level and a decrease of 62,49% at the beginning level. P-value (0,00) is lower than the significance level (0,05). It tested that there is a significant improvement with the application of the blog, over the PAT level.